ANALISIS KEMAMPUAN BERPIKIR KRITIS AUDITOR INTERNAL PADA TAHAP PERENCANAAN AUDIT SISTEM MANAJEMEN MUTU DI UNIVERSITAS SURABAYA - Bella Callista; Fidelis Arastyo Andono (Media Ekonomi, 2012)
This study aims to look at how critical thinking skills when planning the audit of quality management system at the University of Surabaya. The background of this research is because there has been no previous study that discusses the critical thinking skills and their relation to the audit planning process. In its practice, this study used a qualitative approach and can be categorized as basic research by conducting interviews and document analysis as the primary method for obtaining the data. It is intended that the results of this study can actually see how the role of critical thinking skills of internal auditors during audit planning. The interviews were conducted at 3 Ubaya internal audit staff. In the other, the analysis is done using several documents were obtained as a result of information that reinforces interviews. From these results, it was found that there is a role of the auditor’s ability to think critically when planning the audit of quality management system in Ubaya. In addition, critical thinking skills possessed by the auditor may develop through experience and the training.Keywords: Internal Internal audit, critical thinking, quality management system.